Indigenous MSMEs Financial Management in Rejoso: Empowerment Issues Towards A New Era of Financial Inclusion - Nurlita Novianti; Nadafajar Nurmani'ah Widianti (Journal of Interdisciplinary Socio-Economic and Community Study, 2021)
During the pandemic, MSMEs suffered a drop in demand for goods and services, resulting in a decline in MSME income. The epidemic had an impact on sales, which caused a fall. The tourism sector has taken the brunt of the damage. A company in Rejoso Village, Batu, was one of the severely impacted MSMEs. This Village is meant to be an instructive trip in the guise of an MSME Village. The redevelopment of Rejoso Village has a lot of potentials. On the other hand, MSME owners lack financial understanding, making growth challenging for MSMEs. This community service aims to help MSMEs better grasp financial education and create financial reports that capital lenders want. Training and mentoring for MSME owners are among the activities conducted. The method applied is community-based participatory research (CBPR), which includes laying the groundwork, planning, acquiring information, taking action, monitoring and assessment, and evaluation. This activity produces a financial statement that can be used to make MSME business choices.